Management of Melaleuca by Professional Land Managers in South Florida - Katherine Carter-Finn; Alan W. Hodges; Donna J. Lee; Michael T. Olexa (EDIS)
FE671, a 13-page fact sheet by Katherine Carter-Finn, Alan W. Hodges, Donna J. Lee, and Michael T. Olexa, describes the results of a survey of professional land managers conducted in the 10 southernmost counties of Florida. Includes references and 12 tables. Published by the UF Department of Food and Resource Economics, November 2006.